2017
DOI: 10.1080/08830185.2017.1401620
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of regulatory T cells infiltration in HER2-enriched breast cancer microenvironment

Abstract: Breast cancer represents a complex and heterogeneous disease that comprises distinct disease conditions, histological features, and clinical outcome. Since many years, it has been demonstrated as an association between HER2 amplification and poor prognosis, because its overexpression is associated with an aggressive phenotype of breast tumor cells. A significant proportion of cases have developed resistance to the current therapies available. Consequently, new prognostic markers are urgently needed to identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 63 publications
1
7
0
Order By: Relevance
“…In the current study, there is a high immune response illustrated by high expression of CD8, FOXP3 and CD68, which play an important role in tumour microenvironment and immune response, to ISG15 protein expression which may also support the role of ISG15 in controlling tumour microenvironment in BC. It is well known that the tumour microenvironment has an essential role in stromal infiltration, invasion and development of LVI [52]. Additionally, ISG15 mRNA association with MMPs indicates the role in tumour progression as they have the ability to reorganise the extracellular matrix and prepare the microenvironment to produce cytokines that enhance cancer cell migration and proliferation [53].…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, there is a high immune response illustrated by high expression of CD8, FOXP3 and CD68, which play an important role in tumour microenvironment and immune response, to ISG15 protein expression which may also support the role of ISG15 in controlling tumour microenvironment in BC. It is well known that the tumour microenvironment has an essential role in stromal infiltration, invasion and development of LVI [52]. Additionally, ISG15 mRNA association with MMPs indicates the role in tumour progression as they have the ability to reorganise the extracellular matrix and prepare the microenvironment to produce cytokines that enhance cancer cell migration and proliferation [53].…”
Section: Discussionmentioning
confidence: 99%
“…Although LVI is considered as a prerequisite for tumour metastasis, there are multiple LVI-associated genes/proteins that do not generate metastasis. Banin-Hirata et al [119] investigated a significant role of HER2-positive BC in LVI by enhancing the tumour microenvironment to support the tumour cell growth, stimulating invasion LVI and metastasis. There are several pathways related to cancer cell migration which are essential to the prevention of metastasis, such as P120 catenin, FAK, RhoA, paxillin and P130CAS pathways.…”
Section: Future Directions and Conclusionmentioning
confidence: 99%
“…Moreover, this study has revealed that SEC14L1 protein expression had a significant relationship with HER2 status and high histological grade. We previously reported that definite lymphovascular invasion was significantly correlated with HER2 positivity [1] and tumor microenvironment has a crucial role in the HER2 signaling pathway, invasion, and metastasis, including the development of lymphovascular invasion [27,28]. A previous study suggested that SEC14L1 might have an important role in trafficking proteins on cell membrane [29].…”
Section: Discussionmentioning
confidence: 97%